An environmental scan of current mentorship: fostering the next generations in cardiothoracic surgery in the UK - Michelle Lee; Georgia R. Layton; Elizabeth Belcher; Deborah Harrington; Gillian Hardman; Betsy Evans; Narain Moorjani; Karen Booth (Journal of Cardiothoracic Surgery)
Abstract Objectives Mentorship is critical to the professional development of junior colleagues in cardiothoracic surgery. Despite its presumed importance and frequent discussion, its impact within cardiothoracic surgery training remains uncharacterised within the UK. We aimed to evaluate mentorship experience and identify gaps in the system of mentorship education. The differences between men and women’s views on mentorship are also considered. Methods We prospectively collected of 92 responses [50 M:42 F] over 18 weeks. ‘Society for Cardiothoracic Surgery in Great Britain and Ireland (SCTS) Critically Appraising mentorship’ survey was formulated using electronic questionnaire system and distributed via emails to health professionals and medical students by using SCTS membership directory. The survey domains explore respondents’ demographics, current or previous academic appointments, leadership roles, experience of mentorship, and opinions regarding ideal implementation of mentorship model, including the views on necessity for racial and gender concordance between mentor and mentee. Results 43% of respondents (40/92) had less than 5 years of experience in practice, but in general men were more experienced than women with over 15 years of practice (40% versus 9.52%) (p = 0.01). Women are more likely to change their practice due to favourable work-life balance (40%, 4/10) or due to financial incentives (40%, 4/10). On the other hand, men were mostly likely to transit due to career specialisation (38.1%, 8/21) (p = 0.014). 48% of respondents (45/92) have a system of mentorship in the current practice, but 66.67% (30/92) did not have formal evaluations. All male participants did not think gender of mentor/mentee was important, but 21.43% (9/42) of women did (p = 0.002). Conclusion The need for mentorship programme is widely recognised and is imperative to achieve maximum career potential, both professionally and personally. The key will be to establish more structured mentoring programme, finding apposite mentor-mentee dyad, predefining mentorship need, and recognising the unique needs associated with the mentee’s identity. Women face unique challenges as a minority, and this must be considered when forming mentorship relationship.